Foucault's Prison? Management Control in an Automotive Distributor - Dopson, S; Cowton, C (2002)
From its roots in the writings of Robert Anthony and his colleagues at Harvard Business School, the field of management control has expanded greatly, drawing on a wide variety of perspectives. With reference to a case study of a British automotive parts distributor, this paper considers the usefulness of a Foucauldian perspective for understanding management control. Some support is expressed for the usefulness of the notions of disciplinary power and surveillance, but it is concluded that, because of the empirically contingent degree of agency that remains available to managers, it is better to appropriate Foucault’s contribution via the work of Anthony Gidd